Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-22490-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of maltose as energy source in protein-free CHO-K1 culture to improve the production of recombinant monoclonal antibody

Abstract: Oligosaccharides are generally considered to be un-utilized for growth of mammalian cells because their permeability across the cell membrane is low. However, in our previous study, we discovered that CHO and HEK293 cells consume maltose in culture media without serum and glucose. This is interesting because the transporter for maltose in mammalian cells has not been discovered to-date, and the only animal disaccharide transporter that is recently discovered is a sucrose transporter. The application of oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, Leong and coworkers have presented evidence for an adaptive response in which maltose can serve as an energy source in protein-free mammalian cell cultures [18,19]. Our studies with cells incubated with and without serum and on incubations of maltose with serumcontaining medium suggest that maltase-containing fetal calf serum was necessary for stimulation of growth by maltose in bladder and colon cancer cells.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, Leong and coworkers have presented evidence for an adaptive response in which maltose can serve as an energy source in protein-free mammalian cell cultures [18,19]. Our studies with cells incubated with and without serum and on incubations of maltose with serumcontaining medium suggest that maltase-containing fetal calf serum was necessary for stimulation of growth by maltose in bladder and colon cancer cells.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the application of a maltose supplement to produce recombinant mAbs in batch and batch feed culture has been verified. The titers of recombinant mAbs were found to increase by 15 and 23%, respectively, and no obvious adverse reaction to the glycosylation spectrum of the antibody was identified ( Leong et al, 2018 ). Combinations of mannose, fructose, galactose, and fucose were added to the medium when glucose was depleted and lactate accumulated in CHO cells.…”
Section: Type and Key Components Of Serum-free Mediamentioning
confidence: 99%
“…Glucose is the typical source of energy for CHO cells because of the ease of transporting it inside the cell via a sodium-glucose linked transporter and a glucose transporter (Leong et al 2017). Consequently, a high concentration of glucose in the medium can increase lactate production, which is detrimental to the growth and viability of CHO cells (Leong et al 2018). Previous studies have shown that other hexoses, such as galactose, mannose, and fructose, improved cell growth and cell viability (Ritacco et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that other hexoses, such as galactose, mannose, and fructose, improved cell growth and cell viability (Ritacco et al 2018). Aside from these, a few studies have used other carbohydrates, such as maltose (up to 100 mM) and trehalose (150 mM), to improve recombinant IgG and bi-speci c antibody production in CHO cells, respectively (Onitsuka et al 2014;Leong et al 2018). Thus, the aims of the present study are to improve recombinant IgA1 production by adapting the stably producing IgA1 CHO-K1 suspension cell line to 150 mM of disaccharide supplementation, namely with sucrose, maltose, lactose, and trehalose, and to evaluate its cell growth, cell viability, glucose consumption, lactate production, speci c productivity, and aggregation.…”
Section: Introductionmentioning
confidence: 99%